Analysis of Classification Society Service Quality Impact on Customer Loyalty Through Co-Creation, Co-Production in Shipbuilding Projects - Arifin Gustian Pramoko; Eric Harianto Eric Harianto (Faculty of Law, Universitas Pekalongan, 2025)
This study investigates the impact of classification societies on customer loyalty in Indonesia's shipbuilding industry, focusing on service quality, co-creation, and co-production. Classification societies establish and enforce technical standards for ship design, construction, and operation. The research evaluates how service quality influences customer loyalty, mediated by co-creation and co-production. A quantitative approach was applied, collecting data from 200 customers of PT. Biro Klasifikasi Indonesia (BKI) and analyzing it using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate a significant positive relationship between service quality and customer loyalty, with co-production exerting a stronger influence than co-creation. The study underscores the importance of effective collaboration and high-quality services in fostering trust and satisfaction. It offers valuable insights for classification societies to enhance strategies, particularly in providing responsive and reliable services.